2021
DOI: 10.1037/pag0000635
|View full text |Cite
|
Sign up to set email alerts
|

Verbatim and gist memory in aging.

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
(95 reference statements)
1
15
0
1
Order By: Relevance
“…On standardized psychological assessments, older adults attain lower scores on tests of recollection and relational/associative memory, while familiarity-based item recognition is largely unaffected by age. [67][68][69][70][71]129 Declining performance on tests of associative/relational memory indicates posterior, as opposed to anterior, MTL dysfunction in older adults. 6,7,130 Consistent with the evidence from cognitive work, Panitz et al 131 reported reduced intra-HP connectivity in older participants, but only in the middle-posterior HP segments.…”
Section: Intra-mtl Functional Connectivity Changes In Normal Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…On standardized psychological assessments, older adults attain lower scores on tests of recollection and relational/associative memory, while familiarity-based item recognition is largely unaffected by age. [67][68][69][70][71]129 Declining performance on tests of associative/relational memory indicates posterior, as opposed to anterior, MTL dysfunction in older adults. 6,7,130 Consistent with the evidence from cognitive work, Panitz et al 131 reported reduced intra-HP connectivity in older participants, but only in the middle-posterior HP segments.…”
Section: Intra-mtl Functional Connectivity Changes In Normal Agingmentioning
confidence: 99%
“…In normal aging, we expected to see a generalized loss of network integrity, consistent with previous observations in other systems, [60][61][62][63][64][65][66] but perhaps more prominently in the PM network given more robust declines in cognitive function ascribed to this network in prior studies of cognitive aging. 6,7,[67][68][69][70][71]…”
Section: Introductionmentioning
confidence: 99%
“…Episodic memory, or memory for events that occurred in a specific time and place (Tulving, 1983), is susceptible to normal age-related deficits (e.g., Naveh-Benjamin & Old, 2008; Zacks et al, 2000) and representational degradation (Abadie et al, 2021; Castel et al, 2007; Greene et al, 2022; Greene & Naveh-Benjamin, 2020; Kensinger & Schacter, 1999; Koutstaal, 2003; Koutstaal et al, 1999; Koutstaal & Schacter, 1997; Luo & Craik, 2009; Radvansky & Dijkstra, 2007; Reder et al, 1986; Schacter et al, 1997; Simons et al, 2004; Stark et al, 2013; Tun et al, 1998). Older adults are less likely to remember specific details in episodic memory but tend to remember less detailed information, including the gist or meaning of an episode (for reviews, see Brainerd & Reyna, 2015; Devitt & Schacter, 2016).…”
Section: On the Relationship Between Working And Long-term Memorymentioning
confidence: 99%
“…We propose that when deciding how harshly to condemn a falsehood, people also consider the truthfulness of its gist-the broader meaning that the statement communicates (Abadie et al, 2013(Abadie et al, , 2017(Abadie et al, , 2021Brainerd & Reyna, 1990;Fukukura et al, 2013;Reyna & Brainerd, 1991;Stahl & Klauer, 2008). We adopt the term gist from cognitive psychology, where it is used to describe the "essence of information" or "fundamental meaning" in a statement (Reyna, 2020).…”
Section: People Judge a Falsehood's Morality Based On The Truthfulnes...mentioning
confidence: 99%